Contact-Engineered Electrical Properties of MoS2 Field-Effect Transistors via Selectively Deposited Thiol-Molecules - Cho, Kyungjune (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.